Pengelolaan Sistem Rekrutmen dan Penempatan Guru di MI Al-Mukhlisin Kota Jambi - Najmul Hayat; Riftiyanti Savitri; Nuraini (JMiE (Journal of Management in Education), 2022)
This study aims to find out and discuss the management in the recruitment and placement of teachers in Madrasah Ibtidaiyah Al-Mukhlisin Jambi City. This research uses a descriptive qualitative approach, with observational research methods, interviews, and documentation. The source of the data was obtained from the Head of the Madrasah, a Teacher who has taught in a Madrasah, and a new Teacher in a Madrasah. The results showed that: 1) The process of implementing teacher recruitment and placement was carried out by the Head of Madrasah and Foundation; 2) Recruitment is carried out when the Madrasa needs a vacant position, and the dissemination of recruitment information in the can be orally; 3) The placement of teachers is carried out by the Head of the Madrasah taking into account the place of residence of the applicant; 4) The obstacle encountered in the recruitment and placement of teachers is that information is not widely spread.